2012
DOI: 10.1161/strokeaha.112.652248
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Cooling Decreases Tympanic and Skin Temperature, But Significantly Increases Blood Pressure

Abstract: Background and Purpose-Localized head and neck cooling might be suited to induce therapeutic hypothermia in acute brain injury such as stroke. Safety issues of head and neck cooling are undetermined and may include cardiovascular autonomic side effects that were identified in this study. Methods-Ten healthy men (age 35Ϯ13 years) underwent 120 minutes of combined head and neck cooling (Sovika, HVM Medical). Before and after onset of cooling, after 60 and 120 minutes, we determined rectal, tympanic, and forehead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…19 Consistent with the 2 recent trials, we found a large drop of in tympanic temperature starting immediately after external head cooling with the Sovika was applied reaching −1.69°C in mean after 1 hour of cooling. 12,13 Others reported a similar decrease of tympanic temperature using different passive head cooling devices. 20,21 Recording brain and tympanic temperature simultaneously, we clearly demonstrate that this drop is a local cooling effect overestimating, by far, the effect on brain temperature.…”
Section: March 2013mentioning
confidence: 81%
See 2 more Smart Citations
“…19 Consistent with the 2 recent trials, we found a large drop of in tympanic temperature starting immediately after external head cooling with the Sovika was applied reaching −1.69°C in mean after 1 hour of cooling. 12,13 Others reported a similar decrease of tympanic temperature using different passive head cooling devices. 20,21 Recording brain and tympanic temperature simultaneously, we clearly demonstrate that this drop is a local cooling effect overestimating, by far, the effect on brain temperature.…”
Section: March 2013mentioning
confidence: 81%
“…This may be attributable to selective brain cooling as concluded by Wang et al 10 or may be a delayed response of bladder temperature during rapid temperature changes when compared with other body core temperatures. 23 Regarding treatment effects on blood pressure Koehn et al 13 and Kallmünzer et al 12 reported conflicting data in healthy volunteers. Interestingly, Koehn et al 13 observed an immediate increase of blood pressure on cooling onset followed by a steady increase over a 2-hour time period, whereas the blood pressure increase in our study was also immediate, but transient (Figure 2).…”
Section: March 2013mentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature readings are routinely obtained on patients to screen for fever and, since 1986, the use of infrared thermometers for tympanic membrane temperature (TMT) measurements has become widespread in hospitals, clinics and medical practitioners’ offices because of their ease of use, rapid results, data storage capability, cleanliness, safety and assumed relationship to core body temperature [1, 2]. Prior research has shown that local alterations of facial, scalp and neck temperatures can impact TMT, presumably due to thermal effects on local dermal blood vessels that share circulation with vessels supplying the tympanic membrane [35]. Increased skin temperature, with concomitant warming of local dermal vessels in that area of the face covered by protective facemasks, results from a barrier effect upon local heat release mechanisms (i.e., facial skin heat convection, radiation and sweat evaporation) and from the trapping of warmed exhaled air in the mask deadspace [68].…”
Section: Introductionmentioning
confidence: 99%
“…The biological factors that are sensitive to temperature in the whole animal, such as systemic or cerebral blood flow, blood pressure, and the affinity of oxygen to hemoglobin [53,109,4,72], were not present in the current preparation. As such, in the current study, it is not possible to account for the complex physiological environment of the brain and the network between brain and periphery.…”
Section: Discussionmentioning
confidence: 99%